Analysis of Interest in Using Shoopepay Among Millenials Using the Technology Acceptance Model - Kraugusteeliana, Kraugusteeliana; Bakri, Asri Ady; Mustain, HM. Mudjib; Budiyanto, Nugroho Eko; Sutrisno, Hadi (PT Mattawang Mediatama Solution, 2023)
The objective of this research endeavour is to analyse the impact of perceived expediency, usefulness, risk, and utility on the millennial generation's inclination to utilise ShopeePay. The study's population comprises millennials who are users of ShopeePay or have access to the service. An example of 90 respondents will be selected from this population to participate in the research as subjects. The methodology employed for data analysis in this study is multiple linear regression. This study employs quantitative approaches, specifically Simple Random Sampling and Likert scales, to assess the attitudes, opinions, and perceptions of the participants. Perceived convenience had no positive and statistically significant effect on the influence of ShopeePay usage among millennials, according to the findings. However, the influence of ShopeePay usage on the millennial generation is positively and significantly impacted by the second independent variable, perceived utility, the third independent variable, perceived usefulness, and the fourth independent variable, perceived risk. This study's implication is to concentrate the analysis on a single form of electronic wallet, ShopeePay, through an examination of its impact on interest in utilising the ShopeePay electronic wallet.